Damsel - Skye, Evelyn (Random House Worlds, 2023)
"A damsel in distress takes on the dragon herself in this epic twist on classic fantasy-a groundbreaking collaboration between New York Times bestselling author Evelyn Skye and the team behind the upcoming Netflix film Damsel, starring Millie Bobby Brown"--